APPLICATION OF CRITICAL DISCOURSE ANALYSIS (CDA) METHODS TO IMPROVE THE ABILITY OF STUDENTS UNDERSTAND DESCRIPTIVE TEXT - Numertayasa, I Wayan (Universitas Pendidikan Ganesha, 2017)
The present classroom action research aimed to (1) determine the critical discourse analysis method to improve the seventh E grade students of SMP Negeri 1 Susut in comprehending descriptive text, (2) determine the syntaxes of the critical discourse analysis method to improve the seventh E grade students of SMP Negeri 1 Susut in comprehending descriptive text,, (3) determine the responses of the seventh E grade students of SMP Negeri 1 Susut in comprehending descriptive text during the application critical discourse analysis method. The type of the present research is the Classroom Action Based Research (CAR). The subjects were VIIE grade students of SMP Negeri 1 Susut that consist of 33 people. Data collection methods used in this research are the method of observation, tests and questionnaires (questionnaire). Data were analyzed using two (2) analysis model, namely qualitative and quantitative descriptive analysis. The result of this study is the Application of Critical Discourse Analysis (CDA) can improve the ability to understand the descriptive text at seventh E grade students of SMP Negeri 1 Susut in the academic year 2015/2016. It can be seen from the students ability to understand the text from the intial data to the first cycle with an average yield of 17,55 and from the first cycle to the second cycle increase in average yield of 14,64. In accordance with these findings suggested, results of this research can be considered to conduct the study with the same study and deeper.